Galileo Still Goes to Jail: Conflict Model Persistence Within Introductory Anthropology Materials - Aechtner, Thomas (Zygon, 2015)
Historians have long since rejected the dubious assertions of the conflict model, with its narratives of perennial religion versus science combat. Nonetheless, this theory persists in various academic disciplines, and it is still presented to university students as the authoritative historical account of religion-science interactions. Cases of this can be identified within modern anthropology textbooks and reference materials, which often recapitulate claims once made by John W. Draper and Andrew D. White. This article examines 21st-century introductory anthropology publications, demonstrating how such works perpetuate religion-science myths and the notion that history has been replete with inevitable religion versus science warfare. In particular, this study reveals how such introductory materials propagate discord narratives associated with the Scientific Revolution and the Enlightenment. Affiliated with these anecdotes are oversimplified accounts of religious responses to heliocentrism and evolutionary theory, as well as claims that science has invariably led to the usurpation of religious belief and secularization from Galileo onwards.